A Case of Obstructive Jaundice Caused by Metastasis of Ovarian Cancer to the Duodenal Major Papilla. Issue 11 (January 2018) - Takasaki, Yusuke; Irisawa, Atsushi; Shibukawa, Goro; Sato, Ai; Abe, Yoko; Yamabe, Akane; Arakawa, Noriyuki; Maki, Takumi; Yoshida, Yoshitsugu; Igarashi, Ryo; Yamamoto, Shogo; Ikeda, Tsunehiko; et al.
Ovarian cancer often occurs distant metastasis to the peritoneum, liver, lungs, and lymph nodes. However, there has been no reported case of direct metastasis to the duodenal major papilla. We herein reported 72-year-old woman with history of ovarian cancer surgery 11 years ago presenting with obstructive jaundice. Abdominal CT showed a small mass in the distal bile duct. Forceps biopsy from the small mass was done under endoscopic retrograde cholangiography, and histologic examination revealed adenocarcinoma. Pancreaticoduodenectomy was performed and diagnosed immunohistochemically direct metastasis to the papilla from ovarian cancer. The duodenal major papilla is known to be rich in lymph vessels, and these lymph vessels are considered the likely pathway of metastasis in this case.